AN INVESTIGATION OF INDONESIAN STUDENTS’ ABILITY IN PRODUCING THE THIRD PERSON SINGULAR /S/ IN SPEAKING - Fitriah Fitriah (IJEE (Indonesian Journal of English Education), 2014)
This study examined the ability of Indonesian students in producing the third person /s/ in speaking. Seven respondents were presented with two speaking tasks and questions related to their daily activity and picture descriptions. Overall, results showed that the majority of the respondents were able to produce agreement in speaking, although only five respondents could produce agreement correctly above 30%. Therefore, the study suggested that strategies other than speaking should be examined if they could better facilitate students’ production of the third person singular /s/. In the last decade, psycho linguistics has shown strong interest in the production of subject-verb agreement. Several studies have identified the types of errors that most frequently occur in language production. These studies report observations on agreement errors in oral English (Haskel & Macdonald 2005; Hartsuiker & Barkhusyen 2006; Johnson, Villiers & Seymour 2005; Johnson 2005), written French (Hupet, Fayol & Schelstraete 1998; Fayol, Hupet &Largy 1999; Largy & Fayol 2001) and written German (Hemforth & Konieczny 2003). One example of a study which observed agreement errors in oral English was conducted by Haskel and Macdonald (2005). They examined agreement with disjunctive subjects which contained plurality nouns (singular-plural noun and plural- singular noun, e.g. have/has the president or the senators read the documents yet?). The research proved that in relation to agreement with disjunctions like „the president or the senators‟, English speakers tend to prefer a verb form that agrees with the nearer of the two nouns (Haskel & Macdonald, 2005). An investigation of working memory affecting the production of agreement errors in speaking was conducted by Hartsuiker & Barkhusyen (2006). To manipulate the availability of working memory, half of the participants had to remember the list of words while performing the primary (load condition) and half of the others performed the primary task without a memory load. All participants were given the speaking span test and had to perform under specific time constraints. The researchers assumed that agreement errors would occur more frequently in the load condition than in the no-load condition. In this study, there were 64 subjects from the University of Nijmegen participating; they were all native speakers of Dutch. In the presentation of the speaking span test in the load condition, the participants were presented with an adjective (e.g. large) that was followed by a sentence fragment (e.g. the cup for the winners). In the no-load condition, the adjective and sentence fragment were presented at the same time. Then, the participants were instructed to repeat and complete each fragment so they berita terkini indonesia had a full sentence, using the adjective (e.g. the cup for the winners was large) before the deadline. In this experiment, the result confirmed the researchers’ hypothesis that agreement errors were more common in the load condition than in the no-load condition, and the errors occurred more frequently when the head noun was mismatched in the number with the local noun (e.g. the colour on the canvasses). Though there are many research studies on verb agreement, in my study, a different attempt was made to elicit the respondents’ ability in producing the third person /s/ in speaking. I chose not to use complex subjects (which have plurality of the head noun and the local noun). I preferred obvious subjects, for example, ‘she, he, the girl, the boy’ (from which the number of the subjects is clear). The goal of the study was to examine the ability of Indonesian students to produce third person singular /s/ in speaking. I analyzed only the productive of agreement markers (there is /s/ inflection), such as, she walks, the girl works, he cleans. In conjunction with this stated purpose, the following research questions guide the current study: 1. Do advanced learners produce third person /s/ in speaking? 2. How well do they produce the third person /s/ in speaking?